2020
DOI: 10.36387/jifi.v3i2.532
|View full text |Cite
|
Sign up to set email alerts
|

UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN BUAS-BUAS (Premna serratifolia L.) ASAL KABUPATEN MELAWI PROVINSI KALIMANTAN BARAT DENGAN METODE DPPH

Abstract: Buas (Premna serratifolia L.) contains secondary metabolites of flavonoids, saponins, tannins and triterpenoids/steroids, where flavonoids are known to have antioxidant properties and counteract free radicals. Antioxidants are compounds that can fight toxic hazards and reduce cell damage to the body caused by free radical oxidation. The purpose of this study was to determine the antioxidant activity of ethanol extracts of buas-buas leaves was carried out by DPPH (2,2-diphenyl-1-picrylhydrazyl), using UV-Vis sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Penggunaan sebagai obat tradisional tanaman buas-buas oleh masyarakat digunakan untuk masuk angin, bau nafas, infeksi cacing, dan memperbanyak ASI wanita menyusui. Skrining fitokimia menunjukkan daun buas-buas memiliki metabolit sekunder seperti flavonoid, saponin, tanin, steroid/terpenoid [3].…”
Section: Pendahuluanunclassified
“…Penggunaan sebagai obat tradisional tanaman buas-buas oleh masyarakat digunakan untuk masuk angin, bau nafas, infeksi cacing, dan memperbanyak ASI wanita menyusui. Skrining fitokimia menunjukkan daun buas-buas memiliki metabolit sekunder seperti flavonoid, saponin, tanin, steroid/terpenoid [3].…”
Section: Pendahuluanunclassified
“…Research states that Premna serratifolia L. leaves contain secondary metabolites of flavonoids, saponins, tannins, and triterpenoids/steroids, where flavonoids are known to have properties as free radical scavengers or antioxidants, inhibitors of hydrolysis and oxidative enzymes, and work as an antiinflammatory (Liya, 2016). Puspita, W., et al (2020) stated that the ethanol extract of Premna serratifolia L. leaves a very high antioxidant activity with an IC50 value of 20.66 μg/mL. Antioxidants for facial skincare would be better *Corresponding author : Weni Puspita Email : weni.puspita.apt@gmail.com formulated in a topical form than oral because the active substances will interact longer with facial skin (Sutriningsih et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The ethanol extract of bebuas leaves contains flavonoid compounds which are known to have antioxidant properties and ward off free radicals. Based on the results of the research conducted by Puspita et al, it can be concluded that the ethanol extract of P. serratifolia leave has a very high antioxidant activity with an IC 50 potential of 20.66 g/mL antioxidant activity15 .…”
mentioning
confidence: 99%
“…Premna serratifolia L. contains secondary metabolites of flavonoids, saponins, tannins, and triterpenoids/steroids 15 . Methanol extract of P. serratifolia ripe fruit contains saponins, polyphenols, flavonoids, and terpenoids-steroid compounds.…”
mentioning
confidence: 99%